The water-energy-food nexus: An integration agenda and implications for urban governance. (November 2017) - Artioli, Francesca; Acuto, Michele; McArthur, Jenny
Abstract: The water-energy-food nexus has achieved considerable prominence across academic research and policy sectors. The nexus sets an imperative for integrated management and policymaking, centring on the potential trade-offs and complementarities between interdependent water, energy and food systems. Applications of the nexus focus largely on technical or managerial solutions and calls to acknowledge the political dimension of nexus interdependencies have implications for governance at the urban scale. This paper aims to 'urbanise' the nexus agenda and consider the implications of policy integration for urban governance. This examines the nexus in the context of current approaches to urban governance and power relations shaping the provision of water, energy and food in urban areas. Urban infrastructure networks underpin these resource systems and related management systems, although their management tends to operate in silos, with little joint decision-making and planning. Three hypotheses about the interplay between integrative policy framings and urban governance are explored to reconcile integrative policy framings at the urban scale: the appropriation of the nexus narrative by urban governments; re-establishment of political power through integrated management, and implementation of the nexus through smart city approaches. These hypotheses progress the political dimension of the nexus debate and reflect on the role of urban governance in addressing global challenges.